APAKAH KINERJA KEUANGAN DAPAT DIPENGARUHI OLEH INTENSITAS ASET BIOLOGI DAN AKUNTANSI HIJAU (Jurnal Riset Akuntansi, 2022)
Abstract This study aims to examine the effect of biological asset intensity and green accounting on Financial Performance. Quantitative research method with Multiple Linear Regression model is used as an analytical tool. Samples were taken using a purposive sampling technique as many as 90 years of agricultural companies. The results empirically prove that Biological Asset Intensity has no effect on Financial Performance in agricultural companies, Green Accounting has an influence on financial performance of agricultural companies, there is no relationship between Biological Asset Intensity and Green Accounting, and Biological Asset Intensity and Green Accounting together have an influence on the Financial Performance of agricultural companies listed on the IDX in 2017-2019.